The educational values of time in the Holy Quran: An objective analytical study - Chenene, Abdelhafid (The International tax journal, 2025)
This paper highlights an important subject in human life, frequently mentioned in numerous verses of the Holy Quran, which is inseparable from human lifespan — namely, the topic of time in the Quran. This article aims to emphasize the great status of time, in addition to its educational values that contribute to building the personality of the believing individual, affirming their responsibility towards time, and investing life’s moments in righteous deeds. The study also addresses the educational foundations established by the Quran in dealing with time and analyzes some Quranic models that highlight the value of time in the lives of the Prophets and the believers. The study concludes that time holds a magnificent status in the Quran because it is linked to human life; it is the field for righteous deeds that benefit the believer in this world, leading to a sound life, and its proper utilization benefits them in the Hereafter.